Effect of Exchange Rate Volatility on Tax Revenue Performance in Sub-Saharan Africa - Isaac Kwesi Ofori; Camara Kwasi Obeng; Peter Yeltulme Mwinlaaru (ZBW - Leibniz Information Centre for Economics, 2021)
Efforts to spur growth in sub-Sahara Africa have been intensified amid structural and institutional constraints. Tax revenue, the chief source of funding for developmental purposes in SSA remains low and unstable. In fact, the SSA sub-region finds it difficult generating tax revenue up to 20 per cent of GDP. One factor that has not caught the attention of policymakers in terms of its impact on tax revenue performance is exchange rate volatility. Using macrodata spanning 1984 to 2017 for 21 countries, we provide empirical evidence from a panel autoregressive distributed lag technique to show that exchange rate volatility is directly harmful to tax revenue performance, and indirectly through trade openness.
Keywords: E6; F14; F31; F4; F6; H2; O55; 330; Cointegration; Exchange Rate Volatility; GARCH; Sub-Sahara Africa; Tax Revenue